2022
DOI: 10.1038/s41433-022-02261-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment, investigation, diagnosis and initial management of cerebral visual impairment: a consensus practice guide

Abstract: Cerebral Visual Impairment (CVI) is a common condition in the UK. Patients with conditions associated with CVI are frequently seen in paediatric ophthalmology clinics offering eye care professionals an opportunity to identify children proactively. In most cases CVI occurs as part of a neurodevelopmental condition or as a feature of multiple and complex disabilities. However, CVI can also be seen in children with apparently typical development. In some cases, high contrast visual acuity is normal and in other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The analysis of the vision assessments on the 23 children who warranted further visual testing identified that 17 out of 23 had a verifiable reason or clinical findings that would make a result that was outside the normative range in the Austin Assessment a reliable true positive, and not just for CVI related visual issues (Table 3). Using the criteria outlined by Pilling, Allen [8], five children were identified as CVI being highly likely (meeting all three criteria),…”
Section: Phase Twomentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis of the vision assessments on the 23 children who warranted further visual testing identified that 17 out of 23 had a verifiable reason or clinical findings that would make a result that was outside the normative range in the Austin Assessment a reliable true positive, and not just for CVI related visual issues (Table 3). Using the criteria outlined by Pilling, Allen [8], five children were identified as CVI being highly likely (meeting all three criteria),…”
Section: Phase Twomentioning
confidence: 99%
“…The children that do get referred for an ophthalmic assessment for suspicion of CVI are generally those with low visual acuity and a known medical history that is suggestive of CVI. However, as highlighted by Pilling, Allen [8] while a known medical risk factor can be an indicator for CVI, not all children with CVI will present with a known medical event that resulted in their visual issues. This is supported by Chandna, Ghahghaei [18] who highlight that normal visual acuity and absence or presence of neuroimaging findings no longer excludes a diagnosis of CVI.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…CVI is an umbrella term encompassing a variety of visual dysfunctions as a consequence of brain injury, malformation, and/or genetic disorders [ 15 ]. Generally speaking, children with CVI may be placed into one of four profiles based on the severity of functional impact [ 16 ]; in each profile, the extent of the visual dysfunctions are beyond what may be expected due to any potentially co-occurring ocular visual impairment [ 17 ]. While many individuals with CVI demonstrate dorsal stream dysfunctions, such as impairments in visual attention and motion perception [ 18 , 19 , 20 ], many may also exhibit ventral stream dysfunctions.…”
Section: Introductionmentioning
confidence: 99%